Promoting diversity through developing a sense of community - Moys, Jeanne-Louise (International Journal for Students as Partners, 2018)
This case study explores how a students-as-partners approach is helping students in the Graphic Communication programme at the University of Reading gain experience of community through a curriculum design project. The “I am, we are … different by design” project began as a partnership initiative aimed at identifying strategies to extend students’ experience of diversity in the curriculum. Drawing on a mid-project evaluation, the case study presented here explores student partners’ perceptions of achievements and challenges, including developing a sense of community and the impact on career development. It also highlights how supporting opportunities for visibility and recognition throughout a project may contribute to sustaining a culture of reciprocity in partnership.